STRATEGI KOMUNIKASI PERSUASIF KANTOR URUSAN AGAMA (KUA) DALAM MENSOSIALISASIKAN PENCEGAHAN PERNIKAHAN DINI (Studi di Kecamatan Sinjai Utara Kabupaten Sinjai) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem in this study is the persuasive communication strategy of the religious affairs office (KUA) in socializing the prevention of early marriage in North Sinjai District, Sinjai Regency. Then the subject matter is further divided into several sub-problems, namely: 1) how is the persuasive communication process of the religious affairs office in socializing the prevention of early marriage in North Sinjai District, Sinjai Regency? 2) What are the inhibiting and supporting factors of KUA in socializing the prevention of early marriage in North Sinjai District? This type of research is descriptive qualitative research. Data collection techniques use observation, interviews, and documentation. Testing the validity of the data is carried out by increasing the diligence of reading repeatedly, and examining library materials and documents which are referenced in this study. The result of this study is that the persuasive communication of the religious affairs office (KUA) in socializing the prevention of early marriage in North Sinjai District, Sinjai Regency is first, clarity of purpose. Second, think carefully about the person at hand. Third, choose the right communication strategy. The inhibiting factors faced are different perceptions of society and inadequate levels of education. Supporting factors are adequate facilities and infrastructure, the existence of community groups, ta'lim assemblies that help in socializing the prevention of early marriage.